Education as an Instrument of Russian “Soft Power” in Russian-Mongolian Relations at the End of XX - Beginning of XXI Centuries - I. G. Aktamov (Научный диалог)
The article is devoted to the analysis of the development of cooperation in the field of education between Russia and Mongolia in recent history. The transformation of bilateral ties in the educational sphere under the influence of various factors is discussed in the study. Attention is paid to the prerequisites for reducing the intensity of bilateral contacts, as well as the implementation of specific projects that, to one degree or another, stimulate the growth of academic mobility. It is shown that the historical processes of the late twentieth century in Mongolia had an impact on the cooling of relations between countries. It is noted that in the 2000s, Mongolian-Chinese relations, including in the humanitarian sphere were intensified. It is affirmed that China’s “soft power” in the form of various kinds of programs for young people is systemic and influences the formation of public consciousness in relation to the “southern neighbour”. The author considers it necessary to recognize that, for objective reasons, Russia is inferior to China in the field of humanitarian projects. At the same time, the benevolent attitude towards the Russians and to Russia as a whole on the part of the population of Mongolia, especially the older generation is noted. The relevance of the study is to identify trends, factors that determine the nature of the mutual influence of Russia and Mongolia in the field of education in the latest period of historical development. The nature of the interaction of Mongolia and the regions of Russia and their role in the development of bilateral relations are analyzed.